Automated spontaneous breathing trial performance tool is associated with improved outcomes following pediatric cardiac surgery: A single-center retrospective study from Alabama, USA - Matthew G. Clark; Santiago Borasino; Hayden J. Zaccagni; Shannon Payne; Justin Raper; Jeremy Loberger; Kristal M. Hock; Ahmed Asfari (Journal of Pediatric Critical Care)
Background: Extubation failure is associated with significant morbidity, including prolonged time on ventilator and longer hospital length of stay (LOS). Extubation readiness is assessed with a variety of tools. Using algorithmic analysis, we developed a spontaneous breathing trial (SBT) performance tool based on near real-time clinical and ventilator data. We present analysis before and after SBT tool implementation on patients undergoing cardiopulmonary bypass surgery. Subjects and Methods: Retrospective study of patients <21 years old admitted to tertiary cardiac intensive care unit (CICU) June 2019–January 2023. Time to first extubation, total time of ventilation (TOV), LOS, and extubation failure rates before and after deployment of SBT tool after adjusting for age, presence of syndrome, and surgical complexity were compared. Results: Seven hundred and eighty-seven surgical hospitalizations included, 581 preintervention and 206 postintervention. No significant differences in distribution of age groups, frequency of syndrome diagnosis, or surgical complexity between both groups. SBT tool deployment was associated with a 30% reduction in postoperative TOV (incidence rate for post-SBT tool is 0.7 times incidence rate for pre-SBT tool, P < 0.0001) and postoperative LOS by 20% (0.81, P < 0.01). Neonatal subgroup analysis (n = 145) showed SBT tool implementation not associated with a decrease in TOV but was associated with lower extubation failure, 0% versus 13% (P < 0.01). Conclusions: Deployment of physiology-based, real-time, automated SBT tool in a single pediatric CICU was associated with decreases in TOV and LOS as well as a decrease in extubation failure among neonates.